The Differential Risk Transfer: a new approach for reducing vulnerability to climate-related hazards - Fernández Lopera, Cristian Camilo (2022)
Purpose – Climate-related disasters are the most representative in terms of recurrence and impacts. To reduce them, risk transfer is a key strategy for climate risk management. However, this approach does not consider the socioeconomic vulnerability of each population group, limiting its effectiveness. The objective of this paper is to improve and increase the usefulness of risk transfer through the Differential Risk Transfer (DRT) approach. Design/methodology/approach – A comprehensive and systematic review of the state of the art on Differential Approach (DA) is presented, and its connection with existing models of vulnerability to disasters is analysed. Through epistemic deliberations, an operational definition of Differential Risk Transfer (DRT), as well as its advantages are discussed. Finally, general guidelines are presented for the implementation of the DRT in a specific context. Findings – The results confirm that DA presents a clear relation with the models for the study of disaster vulnerability. The small group discussions agree with the usefulness of DRT for improving climate-related risk management. Practical implications – This paper argues for the inclusion of the DRT approach in the climate risk management strategies aiming to fill the disaggregated data gaps that limit the potentiality and accuracy of risk transfer schemes worldwide. Originality/value – This innovative approach improves the accuracy of the risk transfer mechanisms through the recognition of the differences of ethnicity, gender and life cycle that increase socioeconomic vulnerability to climate-related disasters.